Le nuove frontiere dell’operatività nelle maxi emergenze: l’affiancamento dello psicologo alle squadre tecniche - Benedetta Giacomozzi; Marzia Marsili; Ingrid Tere Powell; Gina Riccio; Ilaria Vasselli (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2017)
In this paper, the authors present their field experiences as volunteers of the association “Psicologi per i Popoli − Trentino” in the aftermath of the 24th August 2016 earthquake, which struck especially Amatrice and the neighbouring municipalities. From those experiences, the whish emerged to share an “operational model” concerning the psychologist’s role when collaborating with the technical team responsible for habitability assessment (engineers, architects, surveyors and fire fighters), and helping people to collect their personal belongings from their houses. Hence the need arises to promote an approach towards the integration of the various professional roles which preserves their specificity. A reflective approach would represent a collaborative way of working, a different intervention perspective, and would allow a constructive self-positioning in the situation and context in which everyone operates. Through some reports from the field experience, both with people and technical teams, this paper will underline the importance of an integrated work among professionals involved in the emergency situations with different roles. Some reflections for the future will be provided, particularly about the prevention of burn-out and the training of the technical teams involved in the maxi-emergency context. Thanks to this “operational model”, the inclusion of psychologists in multidisciplinary teams will help in keeping the focus on the fundamental elements of well-being for all the people involved in the different emergency phases.